Variations in bacterial profiles associated with semen collection timing and bull breed, analyzed using 16S rRNA sequencing and MALDI-TOF MS - Cojkic, Aleksandar; Niazi, Adnan; Hansson, Ingrid; Morrell, Jane M. (Frontiers in Veterinary Science, 2025)
IntroductionBacterial contamination can occur at multiple stages of semen processing, necessitating the use of antibiotics in bull semen preservation, mandated by regulatory guidelines. To manage antimicrobial resistance (AMR), targeted antibiotic use based on bacterial identification is essential. This study aimed to characterize bacterial communities in bull semen using metagenomic analysis and MALDI-TOF MS across different semen collection times from the same bulls and between two breeds.MethodsSemen samples were collected from 20 dairy bulls (8 Viking Holstein and 12 Viking Red). Each bull provided three ejaculates within a week: the first after a 96 h since previous collection (T1), the second 48 h later (T2), and the third 24 h after the second (T3). Bacterial species were identified through culturing on cattle blood agar, followed by MALDI-TOF MS identification. Additionally, 16S rRNA sequencing was performed to determine bacterial diversity after DNA extraction.ResultsMALDI-TOF analysis identified 33 bacterial species across 60 semen samples. Six species were exclusive to Viking Holstein (VH) bulls, while 12 were specific to Viking Red (VR) bulls. Certain bacterial species were present only at specific time points: three in the first ejaculate, seven in the second, and five in the third. Across individual bulls, Bacillus spp., Proteus spp., and Staphylococcus spp. were the most consistently detected. Metagenomic analysis revealed 23 phyla and 402 genera in semen samples. Alpha diversity (Shannon index) showed a trend toward p = 0.07 across the bull samples, while beta diversity significantly differed between breeds, with VH samples forming a distinct cluster and VR samples displaying greater microbiome variability. Additionally, specific genera appeared only at one collection time point: Bacteroides, Serratia, Pantoea at T1, Wolbachia, Prevotella, Peptococcus, Alloprevotella at T2, and Streptococcus, Staphylococcus, and Mycoplasma at T3. Specific genera, Acidocella and Escherichia, exhibited negative correlations with most bacterial taxa but showed a slight positive correlation with each other; while Acidocella was detected in nearly all semen samples, except for two samples.DiscussionThe seminal microbiota of bulls varies over time and differs between breeds, indicating that it is influenced by a complex interaction of environmental, physiological, and host-related factors.